2016
DOI: 10.1080/13691457.2016.1155542
|View full text |Cite
|
Sign up to set email alerts
|

Social work education in a time of national crisis in Greece: educating the workforce to combat inequalities

Abstract: Since 2010, Greece has experienced an unprecedented economic and humanitarian crisis, which continues to have tremendous social impact. Austerity measures and policy cuts have included a dis-investment in social work and social care and more recently the abolition of one of the four national Social Work Departments providing qualifying social work education. In this context, this study addresses the following question: how does prequalifying social work education in Greece influence students' ability to manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…An initiative by students and academics along with professionals organised a number of actions to challenge the Ministry's decision. The University premises were occupied for several weeks along with numerous demonstrations and protests by students and academics across the country, who demanded the Plan be withdrawn (Dedotsi, Young & Broadhurst, 2016;Dedotsi & Young, 2019). Despite our struggle against the neoliberal Athena Plan, our students eventually were 'violently attacked by thugs who allegedly attempted to suppress the protest' (Ioakimidis, Cruz Santos & Martinez -Herrero, 2014, p. 295;Teloni, 2013).…”
Section: Sofia's' Storymentioning
confidence: 99%
“…An initiative by students and academics along with professionals organised a number of actions to challenge the Ministry's decision. The University premises were occupied for several weeks along with numerous demonstrations and protests by students and academics across the country, who demanded the Plan be withdrawn (Dedotsi, Young & Broadhurst, 2016;Dedotsi & Young, 2019). Despite our struggle against the neoliberal Athena Plan, our students eventually were 'violently attacked by thugs who allegedly attempted to suppress the protest' (Ioakimidis, Cruz Santos & Martinez -Herrero, 2014, p. 295;Teloni, 2013).…”
Section: Sofia's' Storymentioning
confidence: 99%
“…Kumashiro 2000;2001); social work (i.e. Dedotsi et al 2016;Dedotsi and Young 2018); and health and nursing (i.e. Wallerstein andBernstein 1988, Rozendo et al 2017).…”
Section: The Freirean Educationmentioning
confidence: 99%
“…Dedotsi et al (2016) have observed that whilst some newer modules claim to provide a more structural approach with references to multicultural work, these do not necessarily elevate students' critical consciousness and adherence to professional (anti-oppressive) values. Yet, advancement for social work education is noted in the revised curriculum (2013) of the social work course route in the AEI, where a number of modules refer to human, civil and social rights; national and EU policies; critical social work as well as the current socio-economic crisis' effects on social care.…”
Section: Social Work Education In Greece -A Background Notementioning
confidence: 99%
“…In the years of crisis from 2008 onwards, within a context of austerity, deconstruction of the welfare state, rise of fascism and violation of human rights, 2 a gradual radicalisation and anti-oppressive stance of social work seems to be occurring in Greece (Dedotsi, Young and Broadhurst, 2016;Ioakimidis and Teloni, 2013). This change is reflected not only in the grassroots initiatives by social workers in the community (for example the community interventions of the Greek branch of Social Work Action Network) but also on the very recent politicisation of the Greek Professional Association of Social Workers (SKLE) by participating in strikes and demonstrations against austerity measures and racism (Teloni and Mantanika, 2015).…”
Section: Social Work Education In Greece -A Background Notementioning
confidence: 99%